Investigation of an integrated autothermal reforming (ATR) and SOFC micro cogeneration system for power generation - (:unkn) unknown (My University, 2006)
In today's era of cogeneration (and trigeneration) power and energy plants with higher efficiencies and lower costs and emissions, in the "micro" sizes are becoming more prevalent. We define the term " microcogeneration" as the sizes under 1.0 MW. Cogeneration technologies are conventional power generation systems making use of the energy remaining in exhaust gases, cooling systems, or other energy waste stream. Typical cogeneration prime movers include, combustion turbines, reciprocating engines, boilers with steam turbines, micro turbines and fuel cells (SOFC, MCFC and PEM). There are several methods of producing hydrogen from fossil resources such as natural gas or naphtha, for example steam reforming, partial oxidation and auto-thermal reforming.
Keywords: Fuel cells; Hydrogen; Micro cogeneration; Reforming